Proposals for Antimicrobial Testing Guidelines Applied on Ajowan and Spanish Lavender Essential Oils - Ribeiro, Sofia Oliveira; Fraselle, Stéphanie; Baudoux, Dominique; Zhiri, Abdesselam; Stévigny, Caroline; Souard, Florence (Planta Medica, 2021)
To fight the rising resistance of microorganisms to antibiotics, a strategy followed by several researchers is to focus on natural compounds, such as essential oils, as a source of potent antibacterial compounds. These last decades, hundreds of original papers have been written about microbiological assays that prove the antibacterial activity of essential oils and their use in the medical field. But can we really compare all the data available in the literature when the raw material, the microbiological assays, and/or the strains are different from one article to another? This review will point out the differences and the inadequate practices found in published articles that tested 2 lesser-studied essential oils–Spanish lavender and the ajowan–by the broth dilution method against Staphylococcus aureus, a human pathogenic bacterium. Many pitfalls were found in the literature, for example, a variable chemical composition rarely underlined by the authors, unidentified strains or clinical strains used without a related antibiogram, a lack of quality controls, and the assertion of questionable positive results. At last, some general guidelines that should be followed by every scientific researcher will be discussed.
Keywords: antibacterial activity; broth dilution method; proposed guidelines; Lavandula stoechas; Trachyspermum ammi; Staphylococcus aureus